Structural, chemical and spectroscopic re-examination of type uklonskovite leads to its redefinition. (1st December 2017) - Menchetti, S.; Bindi, L.; Belakovskiy, D.; Zaccarini, F.
The crystal structure and the chemical composition of uklonskovite from the holotype material was reinvestigated to shed light on its correct chemical formula. On the basis of information gained from this characterization, we revised the formula from NaMg(SO4)OH·2H2O to NaMg(SO4)F·2H2O (F instead of OH). A careful analysis of the structural details together with a critical review of all the chemical data listed in the scientific literature for uklonskovite support our redefinition. We also present Raman data for the mineral for the first time. Our proposal was approved by the Commission on New Minerals, Nomenclature and Classification of the International Mineralogical Association (voting proposal 16-J).